Three-dimensional magnetic microscopy of early stage fatigue in WMZ of low carbon steel plates (JIS-SS400). (March 2014) - Kida, K.; Honda, T.; Santos, E. C.; Saruwatari, K.; Uryu, M.; Houri, K.; Tanabe, H.; Kanemasu, K.
Abstract : Cyclic stresses around welding joint part affect the strength of mechanical components. In order to understand the fatigue phenomena caused by the cyclic stresses, non-destructive methods that can be related to number of stress cycles are necessary. In the present work, we used a newly developed scanning Hall probe microscope (SHPM) equipped with a GaAs film sensor and observed three-dimensional magnetic fields of the specimen before and after four-point fatigue testing at room temperature in air. Low carbon steel plates (JIS SS400) were used in the experiments. It was found that the intensity of the magnet field in a direction perpendicular to the specimen surface was strongly affected by the fatigue cycles. This result means that we can evaluate the fatigue in welding joint area using quantitative magnetic field measurements. Furthermore, it was discovered that the key factor to evaluate the fatigue is the range between 'S' and 'N' ('peak to bottom' values) of the magnetic fields. The three-dimensional magnetic fields decrease before the dislocation does not accumulate enough to generate a small crack at the early stage of the fatigue.